The Growth, Composition, and Functional Properties of Self‐Organized Nanostructured ZrO2‐Al2O3 Anodic Films for Advanced Dielectric Applications. (8th September 2021) - Kamnev, Kirill; Sepúlveda, Marcela; Bendova, Maria; Pytlicek, Zdenek; Prasek, Jan; Kolibalova, Eva; Michalicka, Jan; Mozalev, Alexander
Abstract: An aluminum‐on‐zirconium bilayer is anodized in oxalic acid solution to transform the Al layer into porous anodic alumina (PAA); this is followed by the PAA‐assisted re‐anodizing of the Zr underlayer at voltages 40–280 V. The process results in an array of amorphous ZrO2 nanocolumns, 45–330 nm long, partly filling the PAA pores and anchored to a continuous bottom oxide layer under the pores, 20–130 nm thick, comprising a ZrO1.8 spongelike sublayer superimposed on a ZrO1.5 compact sublayer. The thicknesses of the nanostructured and bottom oxides increase linearly with re‐anodizing voltage, disclosing a low film formation ratio of 1.65 nm V −1, which is impossible with anodic ZrO2 . The amorphous ZrO2 nanocolumns embedded in the highly resistive amorphous PAA matrix combined with the laminated bottom oxide reveal a nearly ideal dielectric performance in a wide frequency range (10 −4 –10 4  Hz) complemented by the low leakage currents and high breakdown voltages (up to 280 V). The film permittivity may be tuned, from 11 to 20, by combining the anodizing and pore‐widening techniques. The advantageous architecture, fabrication approach, and functional properties of the films allow the design of a prototype of an emerging hybrid polymer electrolytic microcapacitor for on‐chip integration. Abstract : Novel nanostructured ZrO2 ‐Al2 O3 mixed‐oxide films synthesized via the self‐organized anodizing of Al/Zr metal layers reveal excellent dielectric properties and advantageous structural and morphological characteristics that allow for potential application in emerging electrolytic microcapacitors for on‐chip integration.